Tinjauan Yuridis Terhadap Rencana Pengalihfungsian Lapangan Tenis Di Kota Pangkalpinang - Maulana Wibowo; Kibruazka Enggal Najiyya Kalbu; Taufiiqul Hakim As’ad (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The provision of sports facilities such as sports fields, running tracks, and swimming pools constitutes a standard public amenity provided by local governments to serve as venues for sports activities. Each region allocates land differently for each public facilities. Local governments tend to repurpose sports infrastructure for other facilities, as currently planned in the city of Pangkalpinang. The aim of this research is to examine the regulations and procedures governing the process and responsibilities regarding the repurposing of sports facilities. A normative legal research method with a normative juridical approach was chosen for this study. The findings indicate that the repurposing of sports facilities must adhere to the provisions of the legislation. Local governmets must follow procedures and regulations regardung repurposing. Peraturan Menteri Pemuda dan Olahraga Nomor 9 Tahun 2022 Tentang Tata Cara Peniadaan dan/atau Pengalihfungsian Prasarana Olahraga Aset/Milik Pemerintah Pusat atau Pemerintah Daerah provides technical specifications regarding responsibilities of parties involved in repurposing sports facilities. There are sanctions for those who violate the regulations on repurposing sports infrastructure. It is hoped that through this research, the Pangkalpinang City Government and other parties will take into account the regulations concerning the repurposing of sports facilities.